CD8 T-cell-mediated protection against liver-stage malaria: lessons from a mouse model - Van Braeckel-Budimir, Natalija; Harty, John T. (Frontiers in Microbiology, 2014)
Malaria is a major global health problem, with severe mortality in children living is Sub-Saharan Africa, and there is currently no licensed effective vaccine. However, vaccine-induced protection from Plasmodium infection, the causative agent of malaria, was established for humans in small clinical trials and for rodents in the 1960’s. Soon after, a critical role for memory CD8 T cells in vaccine induced protection against Plasmodium liver-stage infection was established in rodent models and is assumed to apply to humans. However, these seminal early studies have led to only modest advances over the ensuing years in our understanding the basic features of memory CD8 T cells required for protection against liver-stage Plasmodium infection, an issue which has likely impeded the development of effective vaccines for humans. Given the ethical and practical limitations in gaining mechanistic insight from human vaccine and challenge studies, animal models still have an important role in dissecting the basic parameters underlying memory CD8 T cell immunity to Plasmodium. Here, we will highlight recent data from our own work in the mouse model of Plasmodium infection that identify quantitative and qualitative features of protective memory CD8 T cell responses. Finally, these lessons will be discussed in the context of recent findings from clinical trials of vaccine–induced protection in controlled human challenge models.